Debt maturity structure determinants for listed Iberian firms - Amaro, João Pedro Mendes Soares (2021)
This empirical paper aims to examine the determinants of the corporate debt maturity structure of listed Portuguese and Spanish firms, with an overlook of their timely evolution by comparing a sample of 53 firms from 2000 to 2019 and comparing the relevancy of these determinants during the period of 2000 till 2009 and from 2010 to 2019. Considering the current literature, this paper tests firm-level (firm size, debt weight, effective tax rate, maturity matching, profitability, average yield spread, 52-week share price performance) and country-level variables (term premium and inflation rate). The results provided by the OLS Regression Model, Random Effects Model and Fixed Effects Model, show that the current literature still holds mostly true for both Iberian indexes, when looking inside the individual indexes over the entire timespan, some variables do not show the expected results and their time evolution show that some theories are losing momentum on the PSI20 and IBEX35 indexes when comparing the first and second half of the timespan. These include firm size, 52-week share price performance and inflation. The remaining ones resume their theoretical relevance as the expected relation maintains over the course of the entire period.